Current Status of Income Inequality in India: An Analysis (International Journal of Food and Nutritional Sciences, 2022)
This study uses Word inequality report data to analyze the income inequality trends in India after the economic reforms. Economic inequality is the main issue facing economists. Since classical ideology, the debate on globalization, liberalization, privatization, convergence, divergence, and economic inequality has always been critical economic problems. This article explores the income inequality in India between the population groups